Making Natural Dye Powder from Miana Leaves (Coleus scutellarioides (L) Benth) Using the Foam Mat Drying Method - Sri Wahyuni; Sirajuddin Sirajuddin; Fitriyana Fitriyana (Equilibrium Journal of Chemical Engineering, 2025)
Abstract. Food color is one of the things that consumers consider when choosing and sorting food. So the use of coloring in food seems to be a necessity for every food producer. The health impact of using synthetic dyes is a reason for us to go back to nature by using natural dyes. Natural dyes can be an alternative dye that is non-toxic, renewable and environmentally friendly. Miana (Coleous scutellarioides (L) Benth) is a tropical plant that grows wild in Indonesia. This plant contains anthocyanins which have potential as natural dyes. This research aims to determine the effect of maceration time on total anthocyanin coloring powder from miana leaves as a source of natural coloring substances using the foam mat drying method. The research began with preparing the ingredients, then macerating 25 grams of miana leaves using 250 mL of distilled water with varying times of 6, 12, 18, 24, 30 and 36 hours. The maceration results are then filtered and centrifuged. In the foam mat drying method, maltodextrin filler is added with a concentration of 8% and egg white foaming agent with a concentration of 5%. Based on the research results, the best conditions were obtained at a maceration time of 36 hours. The analysis results showed that the dye powder yield was 57.643%, the water content was 2.237%, the solubility was 97.711% and the total anthocyanin concentration was 217.09 mg/L. Keywords:Coleous scutellarioides (L) Benth, Natural Dyes, Foam Mat Drying, Maltodextrin, Egg White